Colorectal Cancer Screening Prevalence, Perceived Barriers, and Preference for Screening Colonoscopy Among Hospitalized Women - Graham, Howard; Kauffman, Regina; Khaliq, Waseem (Turkish Journal of Gastroenterology, 2022)
Background: Barriers to colorectal cancer screening persist despite screening campaigns, especially among women. This study explores the prevalence, preferences, and barriers associated with colorectal cancer screening and evaluates the effect of an inpatient intervention (one-on-one bedside education and handout about colorectal cancer) on screening adherence among hospitalized women. Methods: A prospective intervention study among 510 hospitalized women, who are cancer-free (except for skin cancer) at enrollment, aged between 50 and 75 years was conducted at an academic center. Socio-demographic, family history, and medical comorbidities data were collected for all patients. A post-hospitalization follow-up survey determined the effect of inpatient intervention on colorectal cancer screening adherence. Unpaired t-test and chi-square tests were used to compare characteristics, perspectives, and preferences for screening among adherent and non-adherent groups. Results: Mean age was 60.5 years, 45% reported an annual household income of <20 000, 36% of women were African American, 27% of women were overdue for colorectal cancer screening, and 33% never had a screening colonoscopy. The most frequently reported barriers to colorectal cancer screening were “I have other problems more important than getting a colonoscopy,” “No transportation to get to the test,” and “Not counseled by primary care provider.” Sixty-six percent of the non-adherent women would agree to have an inpatient screening colonoscopy if offered. Conclusion: A significant number of hospitalized women are non-adherent to colorectal cancer screening, while the educational intervention was partially successful in enhancing colorectal cancer screening, most hospitalized women remained non-adherent after hospitalization. A majority of these women were amenable to inpatient screening colonoscopy if offered during a hospital stay Cite this article as: Graham H, Kauffman R, Khaliq W. Colorectal cancer screening prevalence, perceived barriers, and preference for screening colonoscopy among hospitalized women. Turk J Gastroenterol. 2022;33(11):901-908.